The Role of the People's Economic Bank in Dual Regulation in the Implementation and Information of Credit Provision Micro, Small and Medium Enterprises (MSMEs) - Hardi Mulyono Surbakti; Muhammad Himan Fikri; Wahyu Dwi Sulindra; Dina Aprilla; Ayunda Mayona; Dinda Sasmita; Syafrin Ananda Harahap (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Bank Ekonomi Rakyat Mangatur Ganda has great potential in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) through effective credit distribution and targeted information delivery, especially for segments that have not been optimally served. Optimizing the role of banking is carried out through various strategies, such as socializing credit programs, providing convenience in the credit application process, implementing outreach strategies, improving service quality, and financing in potential sectors. In addition, the use of information technology is key to expanding service coverage and increasing operational efficiency. Strategic partnerships with the government, other financial institutions, and MSME communities are needed to create an inclusive and sustainable business ecosystem. With management commitment and implementation of targeted strategies, Bank Ekonomi Rakyat Mangatur Ganda has a great opportunity to significantly encourage MSME growth and contribute to improving the welfare of the wider community.